Lithological Identification using Geoelectric Method in Landslide Area in Bengle Village - Icha Khaerunnisa; Andi; Nugroho Budi Wibowo; Thaqibul Fikri Niyartama (Jurnal Fisika dan Aplikasinya, 2025)
Dlepih Village, specifically in Bengle Hamlet, is an area that experienced a landslide disaster on November 28, 2017. This landslide disaster occurred in a residential area, resulting in the death of 2 people, necessitating mitigation measures. One of the initial steps in mitigation is to identify the lithology in the land-slide area. This study aims to determine the lithology in the landslide area using the Dipole-Dipole resistivity geoelectric method. The resistivity method is used to investigate the subsurface structure of the earth by measuring the resistivity of rock or soil. The mechanism of this method relies on the flow of electric current and the measurement of potential difference, and is calculated based on a certain electrode configuration to obtain a picture of underground resistivity. Data was acquired using a set of Naniura Resistivity Meter instruments on four measurement lines. The measurement paths are located in the Semilir Formation, which consists of sedimentary rocks. The research results show that the landslide area consists of soil layers with a resistivity value of 2.32 Ωm 6.69 Ωm and a thickness of 1.26 m - 11.39 m, claystone layers with a resistivity value of 6.69Ωm - 160 Ωm and a thickness of 11 m - 40.5 m, and andesite rock layers with a resistivity value of more than 160 Ωm and a thickness of 5.25 m - 37.71 m.